2020
DOI: 10.4025/actascianimsci.v42i1.47140
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of powdered and encapsulated probiotic: In vivo study on relative carcass, giblet weight and intestinal morphometry of local duck

Abstract: This research was aimed to evaluate the effect of dietary supplementation of either powdered or encapsulated probiotic on relative carcass, giblet weight and intestinal morphometry of local duck. One hundred twenty male day old duck (DOD) were distributed to 6 different dietary groups, included 2 probiotic forms of either powdered (T1) or encapsulated (T2) and 3 levels: 0% (L0), 0.2% (L1), 0.4% (L2). They were reared using pen cages for 42 days (6 weeks). Observed variables were relative carcass, giblet weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…The results (Table 3) show that the percentage of male local duck offal to live weight is 12.34 ± 1.00%. These results were almost the same as the observations from [36] on the weight of duck offal aged 7 months that were kept organically, which was 154.83 g. The results of previous research showed that ducks supplemented with probiotics in their feed and slaughtered at 6 weeks of age had an 8.30% lower percentage of offal than the results of this study [37]. The weight of the offal of female Peking ducks was 168.8 g, and of male Peking ducks was 129.3 g at the rejected age (27 months) [38].…”
Section: Offal Percentagesupporting
confidence: 89%
“…The results (Table 3) show that the percentage of male local duck offal to live weight is 12.34 ± 1.00%. These results were almost the same as the observations from [36] on the weight of duck offal aged 7 months that were kept organically, which was 154.83 g. The results of previous research showed that ducks supplemented with probiotics in their feed and slaughtered at 6 weeks of age had an 8.30% lower percentage of offal than the results of this study [37]. The weight of the offal of female Peking ducks was 168.8 g, and of male Peking ducks was 129.3 g at the rejected age (27 months) [38].…”
Section: Offal Percentagesupporting
confidence: 89%
“…Antibiotics considered one of the most commonly feed additives used in broilers feed (Cruz et al, 2019) to enhance growth, efficiency and livability of birds. However, scientist discovered that excessive use of antibiotics brings about many problems such as pathogenic contamination, bacterial resistant in the end product and add effort to create sustainable poultry farming (Ardiansah et al, 2020). In addition, the use of antibiotics in therapeutic doses causes residual veterinary drugs in final products (Jeong et al, 2010).…”
Section: Recentmentioning
confidence: 99%
“…When a commercial powdered probiotic cocktail including Lactobacillus fermentum, Lactobacillus acidophilus, and Bacillus spp. was evaluated in duck feed [69]. In comparison to powdered probiotic, formulations containing 0.2 percent and 0.4 percent encapsulated probiotic performed better on relative carcass, villus height, and villus weight.…”
Section: Encapsulation Applied In Probiotics and Nutraceuticalsmentioning
confidence: 99%